Changes in fetal acid base status during intravascular transfusion. Issue 7 (July 1988) - Nicolini, U; Santolaya, J; Fisk, N M; Hubinont, C; Kochenour, N K; Greco, P; Rodeck, C H
Abstract : Umbilical venous pH, PCO2, PO2, and base excess was measured immediately before and after 72 intravascular transfusions in 34 fetuses with erythroblastosis fetalis. In 67 uncomplicated transfusions, infused adult blood led to a mean (95% confidence intervals) fall in pH (0.037, CI 0.029 to 0.044) and base excess (2.03, CI 1.61 to 2.45) and a mean rise in PCO2 (0.24 kPa, CI 0.13 to 0.35). These changes correlated significantly with the increase in fetal haemoglobin and packed cell volume. Five transfusions were associated with complications within six hours: intrauterine death in two, fetal-distress necessitating delivery in two, and preterm labour in one. Two had pre-existing acidosis, whereas two of the three with normal blood gas and acid base measurements before transfusion had acute changes that were outside the normal ranges that had been established in uncomplicated transfusions.